Unilateral Usual Ductal Hyperplasia in A 22 Years Old Male Patient: A Case Report - Setiawan, Kelvin; Rosadi, Bramastha Aires; Lawanto, Terry Renata; Rustamadji, Primariadewi (JBN (Jurnal Bedah Nasional), 2019)
Keywords: Usual Ductal Hyperplasia, Male Breast Tumor, Breast Conserving Surgery, Triple Test Evaluation.